2008
DOI: 10.1137/070685166
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of a Finite Element-Based Space-Time Discretization in Elastodynamics

Abstract: We study a finite element-based space-time discretization of the elastodynamics equation u ε tt − div σ(∇u ε ) − εΔu ε t = 0 for ε ≥ 0, where σ = Dφ and φ is a nonconvex function. The convergence for regularization parameters ε > 0 of iterates to weak solutions and for the limiting problem ε = 0 of iterates towards generalized solutions is shown in a general setting of data. Computational experiments are included to motivate formation and propagation of two-dimensional microstructures for decreasing values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Dolzmann and Friesecke used an implicit time scheme and wondered if a Galerkin type method could be used instead. Later, Feireisl and Petzeltová showed that this can be accomplished [12]; see also the following recent papers [10,18,20] which involved similar existence problems and results.…”
Section: Elastodynamicsmentioning
confidence: 87%
“…Dolzmann and Friesecke used an implicit time scheme and wondered if a Galerkin type method could be used instead. Later, Feireisl and Petzeltová showed that this can be accomplished [12]; see also the following recent papers [10,18,20] which involved similar existence problems and results.…”
Section: Elastodynamicsmentioning
confidence: 87%
“…Existence of Young-measure-valued solutions to the peridynamic problem is shown by applying a Galerkin approximation and investigating the limit of approximate solutions. Young measures in (visco)elastodynamics have been studied, e.g., in [9,32,33]. However, talking about classical nonlinear elasticity theory, mainly gradient Young measures have been considered.…”
Section: Introductionmentioning
confidence: 99%